Noise in linear and nonlinear circuits - Maas, Stephen A. (Artech House microwave library, 2005)
"Noise in Linear and Nonlinear Circuits helps professionals optimize real-world circuit performance, showing how noise in both linear and nonlinear circuits can be analyzed and minimized."--Jacket.